ASAS KOTA BERKELANJUTAN DAN PENERAPANNYA DI INDONESIA - Kuswartojo, Tjuk (Jurnal Teknologi Lingkungan, 2006)
Cities percieved having strategic role for implementing global program onsustainable development as established through Earth Summit at Rio de Janeiro by 1992. It is realized that cities are fundamental for economic opportunities and social interaction, as well as cultural and spiritual enrichment. However, cities also damage the natural environment and exploit natural resources in an unsustainable manner, which can jeopardize long-term prosperity and social wellbeing. This is of global concern, as more than half of the world’s population lives in cities and trends indicate that this will increase. Based on this understanding by 1994 European cities declared Aalborg principles and by 2002 several cities of the world declared Melbourne principles on sustainable cities. The principles are intended to guide thinking and provide a strategic framework for action and allow cities to develop sustainable solutions that are relevant to their particular circumstances. Despite there were Indonesian cities participate in Melbourne conference, sustainable cities is still aliens for most of city governance. Therefor there was initiative to formulate sustainable cities principles that assumed more relevance and appropriate to Indonesian situation.